Culture, campus, and confidence: unpacking discrimination's impact on mental health among diverse college students - Williams, LeNisha; Mullins, Jordan L.; Israel, Bethel; Bravo, Diamond Y.; Loyd, Aerika Brittian (Frontiers in Education, 2025)
ObjectiveThis study examined the associations between discrimination, social anxiety, and self-esteem among racially and ethnically minoritized college students. Additionally, we explored how ethnic-racial identity affirmation, family ethnic socialization, and school ethnic-racial composition influenced these relationships.MethodThe sample consisted of 3,257 Black, Latinx, and Asian American college students (Mage= 19.94) from 30 universities in the United States who participated in an online multi-university study.ResultsFindings revealed that discrimination was associated with increased social anxiety but not self-esteem. We also discovered that school ethnic-racial composition played a role in the relationship between discrimination and self-esteem when diversity was both high and low.ConclusionThese findings highlight the importance of understanding the role of school diversity in students' mental health and provide valuable insight for school personnel and policy makers who are dedicated to promoting more supportive school environments.